Perceived risk and attitude's mediating role between tourism knowledge and visit intention during the COVID-19 pandemic: implementation for coastal-ecotourism management - Zainal Abidin; Wahyu Handayani; Emeraldo A. Zaky; Achmad D. Faturrahman (Heliyon, 2022)
CMC Tiga Warna is one of the coastal area management for conservation and ecotourism in southern Malang, Indonesia. Despite fewer tourist visits, the COVID-19 pandemic did not dissuade locals from managing and protecting ecotourism in the coastal area. This study aims to: (a) to describe coastal ecosystem management; and (b) to analyze coastal ecotourist visit intention related to tourism knowledge, perceived health risk, and risk attitude in the post-COVID-19 era as a part of developing strategy for coastal ecosystem management in the study area from the perspective of ecotourists and destination management. CMC Tiga Warna management, community group supervisors, the local community, and a variety of experts were interviewed in order to gather data for the current strategy. Coastal ecotourist visit intention data from domestic ecotourists was gathered via online and offline surveys. Analyzing the visit intention data with Warp-PLS. Using the visit intention model and interview data, the coastline management strategy was described. This study found that the coastal environment management plan constantly involved ecotourists and locals. Tourism knowledge and risk attitude are positively related to the visit intention, however perceived health risk is negatively related to it. The significant positive relationship between tourism knowledge and ecotourist visit intention is mediated by perceived health risk and risk attitude. Development of the coastal ecosystem management plan could be supported by boosting visit intention, ecotourism visits, or economic incentive as a motive for sustaining the conservation program's consistency, and ecological and social rewards in a sustainable manner. This study added to the Theory of Reasoned Action by adding two additional factors, tourist knowledge and perceived health risk, in addition to the attitude to predict the visit intention. The ecotourism manager should provide varied tourist information and knowledge as needed, reduce COVID-19 exposure risk at tourist destinations, and increase risk attitude.